2021
DOI: 10.1038/s41598-021-83976-6
|View full text |Cite
|
Sign up to set email alerts
|

Distinct chemical blends produced by different reproductive castes in the subterranean termite Reticulitermes flavipes

Abstract: The production of royal pheromones by reproductives (queens and kings) enables social insect colonies to allocate individuals into reproductive and non-reproductive roles. In many termite species, nestmates can develop into neotenics when the primary king or queen dies, which then inhibit the production of additional reproductives. This suggests that primary reproductives and neotenics produce royal pheromones. The cuticular hydrocarbon heneicosane was identified as a royal pheromone in Reticulitermes flavipes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…They represent an effective form of communication in termites, especially in subterranean environments where visual and odorant signals can be less effective (Hill, 2009). Termites are therefore able to transmit different signals using shaking behavior, such as alarm signaling, caste identification and reproductive regulation (Eyer et al, 2021;Pailler et al, 2021). In addition, termites can exhibit different behaviors toward infected nestmates.…”
Section: Introductionmentioning
confidence: 99%
“…They represent an effective form of communication in termites, especially in subterranean environments where visual and odorant signals can be less effective (Hill, 2009). Termites are therefore able to transmit different signals using shaking behavior, such as alarm signaling, caste identification and reproductive regulation (Eyer et al, 2021;Pailler et al, 2021). In addition, termites can exhibit different behaviors toward infected nestmates.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it is likely that other compounds may be responsible for physical queen recognition. Recent observations in the genus Reticulitermes have shown that recognition of reproductives, accompanied by appropriate behavior, is mediated by king/queen-specific CHCs 29,30,45 . Therefore, in line with some predictions (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Observations of king-and/ or queen-specific profiles of CHCs in several termite species indicated that convergently with eusocial Hymenoptera, these non-volatile cues may be involved in fertility signaling 27,28 . CHCs were recently shown to act as releaser pheromones responsible for king and queen physical recognition 29,30 , and pieces of indirect evidence suggest that they may also act as QPPs, inhibiting neotenic formation 31 . Nevertheless, the only termite QPP was identified in 2010 in Reticulitermes speratus (Rhinotermitidae) as a volatile blend of n-butyl-n-butyrate and 2-methylbutan-1-ol 15 .…”
mentioning
confidence: 99%
“…These results show that the development process of queen recognition signals in R. speratus is partly different from the related species, R. avipes. Both of these two species require conspeci c chemical background for neotenic queen recognition However, neotenic queens (and also kings) of R. avipes develop royal-speci c hydrocarbon, which is not present on the cuticles of primary reproductives and non-reproductive castes (Funaro et al 2018;Eyer et al 2021), while queens of R. speratus increase the relative amount of one of the CHCs shared among all castes. These facts suggest that it depends on termite species whether queens synthesize a queenspeci c hydrocarbon or increase the relative amount of one of the pre-existing hydrocarbons as a queen signal.…”
Section: Discussionmentioning
confidence: 99%